Gene panel analysis of 119 index patients with suspected periodic paralysis in Japan - Yuan, Jun-Hui; Higuchi, Yujiro; Hashiguchi, Akihiro; Ando, Masahiro; Yoshimura, Akiko; Nakamura, Tomonori; Hiramatsu, Yu; Sakiyama, Yusuke; Takashima, Hiroshi (Frontiers in Neurology, 2023)
Genetic factors are recognized as major reason of patients with periodic paralysis. The goal of this study is to determine the genetic causes of periodic paralysis in Japan. We obtained a Japanese nationwide case series of 119 index patients (108 males and 11 females) clinically suspected with periodic paralysis, and a gene panel analysis, targeting CACNA1S, SCN4A, and KCNJ2 genes, was conducted. From 34 cases, 25 pathogenic/likely pathogenic/unknown significance variants were detected in CACNA1S (9 cases), SCN4A (19 cases), or KCNJ2 (6 cases), generating a molecular diagnostic rate of 28.6%. Seven variants have yet been found linked to periodic paralysis previously. The diagnostic yield of patients with hypokalemic and hyperkalemic periodic paralyses were 26.2% (17/65) and 32.7% (17/52), respectively. A considerably higher yield was procured from patients with than without positive family history (18/25 vs. 16/94), onset age <= 20 years (24/57 vs. 9/59), or recurrent paralytic attacks (31/94 vs. 3/25). The low molecular diagnostic rate and specific genetic proportion of the present study highlight the etiological complexity of patients with periodic paralysis in Japan.